A bimetallic composite catalyst for producing hydrogen by hydrolysis and a preparation method thereof
By loading the bimetallic composite catalyst with nickel-copper alloy particles on reduced graphene oxide, the problem of low hydrolysis performance of magnesium-based hydrogen storage materials is solved, and efficient hydrolysis and hydrogen production effect are achieved, and the dispersion and particle size uniformity of the catalyst are significant. Improve, significantly improve catalytic performance.
Patent Information
- Application Number
- CN202311106590.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-08-30
AI Technical Summary
The existing catalysts have problems of low efficiency and insufficient catalyst stability in improving the hydrolysis performance of magnesium-based hydrogen storage materials, especially when nickel-copper alloy particles agglomerate and particles grow, resulting in a reduced catalytic effect.
A bimetallic composite catalyst with reduced graphene oxide supported nickel-copper alloy particles is prepared by ultrasonic oscillation, drying and calcination, and the morphology and particle size of the catalyst are controlled to ensure uniform dispersion and high activity of nickel-copper alloy particles.
The efficient hydrolysis hydrogen production performance is achieved. The catalyst significantly improves the hydrolysis performance of magnesium-based materials at low doses, avoids the formation of passivation layers, promotes the diffusion and reaction of hydrogen, and reaches a hydrolysis conversion rate of 98.49%.
Smart Images

Figure CN117123228B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen storage materials, and specifically relates to a bimetallic composite catalyst for producing hydrogen by hydrolysis, a preparation method thereof, and a nano-magnesium hydride-based hydrolysis hydrogen production material prepared by the bimetallic composite catalyst. Background Art
[0002] Catalysts play a very important role in improving the hydrolysis performance of hydrogen storage materials, especially metal hydrides represented by magnesium hydride. They can effectively promote the reaction between materials and water molecules and achieve efficient hydrogen release. An efficient catalyst can greatly improve the hydrolysis hydrogen production performance of the material even if only a small amount is added. Finding a more suitable catalyst to improve the hydrolysis performance of materials has been a hot topic in recent years.
[0003] Commonly used catalysts for hydrogen production by hydrolysis include metals, metal oxides, hydrides and halides. Recent studies have found that metal catalysts have a good effect on improving the hydrolysis performance of magnesium-based hydrogen storage materials. There are several different mechanisms for the catalytic effect, such as adhering to the surface of the material to prevent it from agglomerating and preventing the formation of a passivation layer; forming a channel for hydrogen to diffuse outward easily, promoting water molecules to continuously contact the material until the reaction ends. Therefore, metal catalysts are very ideal catalysts for improving the hydrolysis performance of magnesium-based hydrogen storage materials. Among them, the literature (Phase-structural and morphological features, dehydrogenation / re-hydrogenation performance and hydrolysis of nanocomposites prepared by ball milling of MgH2 with germanium, International Journal of Hydrogen Energy, 44, 23160-23171) introduces metal Ge into MgH2 and uses organic acid as a solution to achieve an excellent performance of nearly 100% conversion rate of hydrogen production by hydrolysis within 1 minute, maximizing the high theoretical hydrogen production of MgH2. In order to ensure the stability of metal particles, they need to be loaded on a carbon material with a high specific surface area. By utilizing the interaction and spatial confinement between the metal and carbon, the particles can be separated from each other to prevent their migration and aggregation, allowing them to exert the highest activity in very small quantities.
[0004] Therefore, there is an urgent need to develop a method for preparing a composite material of multiple metal elements loaded on carbon so that it has good catalytic performance when used in hydrolysis hydrogen production materials, etc. Summary of the invention
[0005] In view of the shortcomings and defects of the prior art, one of the purposes of the present invention is to provide a bimetallic composite catalyst for hydrogen production by hydrolysis. The catalyst has good catalytic performance and can be applied to the fields of catalysts, hydrolysis hydrogen production materials, hydrogen storage materials, battery materials and supercapacitors, and has good performance.
[0006] The present invention also provides a method for preparing a bimetallic composite catalyst for producing hydrogen by hydrolysis, which can effectively control the morphology and particle size of the product, has a simple process, and the obtained product has high purity, good dispersibility of metal particles, uniform particle size and good catalytic performance.
[0007] On this basis, the present invention also provides a nano-magnesium hydride-based hydrolysis hydrogen production material obtained from the catalyst.
[0008] The magnesium hydride of the present invention reacts with water as follows:
[0009] MgH2+2H2O→Mg(OH)2+2H2.
[0010] The technical solution adopted by the present invention to solve the technical problem is as follows:
[0011] A bimetallic composite catalyst for producing hydrogen by hydrolysis, the composite catalyst comprising reduced graphene oxide and nickel-copper alloy particles supported on the reduced graphene oxide. In the composite catalyst, the mass percentage of the reduced graphene oxide is 30%-50%, and the mass percentage of the nickel-copper alloy is 50%-70%. If the content of reduced graphene oxide is too high, the catalytic effect will be reduced; if the content of reduced graphene oxide is too low, it cannot play a good role as a supported alloy catalyst, and will cause the agglomeration of the nickel-copper alloy and the growth of particles.
[0012] In the above-mentioned bimetallic composite catalyst for producing hydrogen by hydrolysis, as an implementation mode, for example, the mass percentage of the reduced graphene oxide is 40%, and the mass percentage of the nickel-copper alloy is 60%.
[0013] A method for preparing a bimetallic composite catalyst for producing hydrogen by hydrolysis, comprising:
[0014] (1) adding a nickel source, a copper source, a carbon source and a surfactant to an organic solvent, ultrasonically oscillating until all of them are dissolved to form a transparent solution, and then stirring to obtain a solution A;
[0015] (2) placing solution A in a forced air oven for drying to obtain a composite catalyst precursor;
[0016] (3) The precursor powder prepared above is calcined to obtain the composite catalyst.
[0017] In the above-mentioned method for preparing a bimetallic composite catalyst for producing hydrogen by hydrolysis, as a preferred embodiment, the mass ratio of the carbon source, the nickel source and the copper source in the steps (1) and (2) is determined according to the mass ratio of the reduced graphene oxide and the nickel-copper alloy in the bimetallic composite catalyst for producing hydrogen by hydrolysis. For example, after corresponding calculation, the mass ratio of the nickel source, the copper source and the carbon source of the present invention can be 1:1:2.28.
[0018] In the above-mentioned preparation method of the bimetallic composite catalyst for hydrogen production by hydrolysis, as a preferred embodiment, in the step (1), the nickel source is nickel nitrate hexahydrate, the copper source is copper nitrate trihydrate, and the organic solvent is not particularly limited (the same below), preferably, the organic solvent is methanol. The present invention uses nickel nitrate hexahydrate and copper nitrate trihydrate with crystal water, the raw materials are cheap, and the production cost can be reduced. It should be particularly pointed out that the present invention has no other special restrictions on the nickel source and the copper source, and other nickel and copper raw materials can also be selected.
[0019] In the above-mentioned method for preparing a bimetallic composite catalyst for producing hydrogen by hydrolysis, as a preferred embodiment, in the step (1), the stirring method is magnetic stirring, and the stirring time is 5.5-6h.
[0020] In the above-mentioned method for preparing a bimetallic composite catalyst for producing hydrogen by hydrolysis, as a preferred embodiment, in the step (1), the carbon source is graphene oxide, and the organic solvent is methanol.
[0021] In the above-mentioned method for preparing a bimetallic composite catalyst for hydrogen production by hydrolysis, as a preferred embodiment, in the step (2), the drying temperature is 55-65°C (such as 56°C, 58°C, 60°C, 62°C, 64°C), and the drying time is 20-40h (such as 25h, 30h, 35h).
[0022] In the above-mentioned preparation method of the bimetallic composite catalyst for hydrogen production by hydrolysis, as a preferred embodiment, in the step (3), the temperature of the calcination treatment is 400-550°C, preferably 450-550°C (such as 455°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 545°C), and the time is 2.5-5h, preferably 3-5h (such as 3.2h, 3.4h, 3.6h, 3.8h, 4h, 4.2h, 4.4h, 4.6h, 4.8h). If the calcination treatment time is too long, the catalyst grains grow, the catalytic activity of the catalyst is reduced, and the performance of hydrogen production by hydrolysis of the composite material is reduced; if the time is too short, it is not conducive to the formation of elemental nickel and cobalt. More preferably, the calcination temperature is 480-520°C (such as 482°C, 485°C, 490°C, 495°C, 500°C, 505°C, 510°C, 515°C); preferably, the calcination atmosphere is a mixed atmosphere of hydrogen and argon.
[0023] In the above-mentioned preparation method of the bimetallic composite catalyst for producing hydrogen by hydrolysis, the raw materials involved in the present invention are all available in the market, for example: the purity of the methanol is ≥99.9%, the nickel nitrate hexahydrate is analytically pure, the copper nitrate trihydrate is analytically pure, and the purity of the graphene oxide is >99%.
[0024] As described above, the present invention has no special requirements on the nickel source, copper source, and graphene oxide, and can be implemented.
[0025] The present invention also relates to a nano magnesium hydride-based hydrolysis hydrogen production material, which contains, in addition to magnesium hydride, a bimetallic composite catalyst for hydrolysis hydrogen production obtained by the above bimetallic composite catalyst for hydrolysis hydrogen production or the above preparation method.
[0026] As described above, a nano magnesium hydride-based hydrolysis hydrogen production material is made of the following components by mass percentage: magnesium hydride: 90-94%, and a bimetallic composite catalyst for hydrolysis hydrogen production 6-10%. Further preferably, the bimetallic composite catalyst for hydrolysis hydrogen production is a reduced graphene oxide-supported nickel-copper alloy composite catalyst. Further preferably, the amount ratio of magnesium hydride to the reduced graphene oxide-supported nickel-copper alloy composite catalyst is 0.92:0.08.
[0027] Preferably, the magnesium hydride and the carbon-supported elemental nickel and cobalt composite catalyst are both in powder form; the purity of the magnesium hydride powder is above 99%, and the particle size is below 40 μm.
[0028] The method for preparing a nano magnesium hydride-based hydrolysis hydrogen production material as described above comprises:
[0029] Pretreatment: according to the ratio of nano-magnesium hydride-based hydrolysis hydrogen production material, magnesium hydride powder and reduced graphene oxide-supported nickel-copper alloy composite catalyst powder are mixed to obtain a mixed powder;
[0030] Post-processing: ball milling the magnesium hydride-based hydrolysis hydrogen production material to obtain a nano magnesium hydride-based hydrolysis hydrogen production material.
[0031] The ball milling method comprises using a ball mill to ball mill the magnesium hydride powder and the reduced graphene oxide-loaded nickel-copper alloy composite catalyst powder, wherein the ball milling mixing is carried out under the protection of an inert atmosphere; the ball milling mixing time is 3-8 hours, more preferably 4-6 hours; the ball-to-material ratio is 35-45:1, the rotation speed is 300-500r / min (for example, it can be 400r / min); and the inert atmosphere is an argon atmosphere.
[0032] For the bimetallic composite catalyst for hydrogen production by hydrolysis of the present invention, the electronic interaction between Ni atoms and adjacent Cu atoms can reduce the binding energy of protons on the active site, thereby enhancing the kinetics of H2 escape and causing lattice distortion after Cu atoms enter the Ni lattice for substitution, thereby enhancing the adsorption capacity of adjacent Ni atoms for active hydrogen atoms. Ni and Cu interact with each other, and simultaneously exhibit a synergistic effect of accelerating charge transfer and increasing the reactive sites on the surface of MgH2. The two together form a channel on the surface of MgH2 that promotes the rapid diffusion of H atoms, which is not only conducive to the continuous escape of H2 bubbles, but also hinders the formation of a continuous Mg(OH)2 passivation layer, so that Mg(OH)2 can only exist in the solution in the form of fragments, thereby promoting the continuous hydrolysis and hydrogen release of MgH2 until the reaction is complete, thereby exhibiting excellent hydrogen production by hydrolysis performance.
[0033] Compared with the prior art, the present invention has the following positive effects:
[0034] (1) The raw materials for the preparation method provided by the present invention are easily available and relatively inexpensive.
[0035] (2) The preparation method provided by the present invention is relatively simple, easy to operate, and has a short experimental period. The liquid phase preparation of the present invention is conducive to the uniform distribution of the catalyst components and can further improve the synergistic catalytic performance.
[0036] (3) The composite catalyst prepared by the present invention contains a metal alloy particle, namely a nickel-copper alloy particle, which has good dispersion when loaded on reduced graphene oxide and a small particle size of about 20-100 nm (as can be seen from the drawings in the reference specification); the carbon material used is not a ready-made material, but is obtained through calcination and reduction treatment; the present invention uses graphene oxide as a carbon source to enable the nickel-cobalt alloy particles to be well loaded on the carbon carrier (there is a chemical bond between the carbon carrier and the metal element).
[0037] (4) The reduced graphene oxide loaded nickel-copper alloy composite material (i.e., bimetallic composite catalyst for hydrogen production by hydrolysis) synthesized by the present invention not only has the excellent properties of carbon materials, but also has the excellent catalytic performance of nickel-copper alloy, and can be more widely used in many fields such as catalysts, hydrogen production materials by hydrolysis, hydrogen storage materials, battery materials, supercapacitors and photoelectric materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can also be obtained based on these drawings.
[0039] Figure 1 This is the X-ray diffraction (XRD) spectrum of the magnesium hydride and reduced graphene oxide-loaded nickel-copper alloy composite material after ball milling in Example 1 of the present invention.
[0040] Figure 2 This is a FESEM image of the reduced graphene oxide loaded nickel-copper alloy composite material of Example 1 of the present invention.
[0041] Figure 3 This is a HRTEM image of the reduced graphene oxide loaded nickel-copper alloy composite material of Example 1 of the present invention.
[0042] Figure 4 This is the EDS energy spectrum of the reduced graphene oxide loaded nickel-copper alloy composite material of Example 1 of the present invention. DETAILED DESCRIPTION
[0043] In order to highlight the purpose, technical solutions and advantages of the present invention, the present invention is further described below in conjunction with embodiments, which are described by way of explanation of the present invention but not limiting the present invention. The technical solution of the present invention is not limited to the specific implementation methods listed below, but also includes any combination of the specific implementation methods.
[0044] The various reagents and raw materials used in the following examples are all commercially available products. The purity of the methanol is ≥99.9%, the nickel nitrate hexahydrate is of analytical grade, the copper nitrate trihydrate is of analytical grade, and the purity of the graphene oxide is >99%.
[0045] Example 1
[0046] A reduced graphene oxide-supported nickel-copper alloy composite material (i.e., a bimetallic composite catalyst for hydrogen production by hydrolysis), wherein the mass ratio of the nickel-copper alloy to the graphene oxide is 2:1.65, and the composite material is prepared by the following method:
[0047] 50 mL of methanol was added to Ni(NO3)2·6H2O (1427.6 mg), Cu(NO3)2·3H2O (1186 mg), GO (400 mg) and PVP (8 mg), and ultrasonic oscillation was performed until all of them were dissolved to form a transparent solution, and then stirred for 6 h. The solution was then placed in a blast oven and dried for 24 h to obtain NiCu@GO. The NiCu@GO powder prepared above was spread in a crucible, placed in a tubular furnace, and heated at 5 °C min under a H2 / Ar atmosphere. -1 The mixture was heated to 500 °C at a heating rate of 100 °C and then cooled naturally after being kept for 4 h to obtain a highly dispersed bimetallic NiCu@rGO catalyst.
[0048] The catalytic performance of the prepared reduced graphene oxide loaded nickel-copper alloy composite material was tested: 0.92g of magnesium hydride powder and 0.08g of reduced graphene oxide loaded nickel-copper alloy composite material were put into a ball mill, wherein the ball milling process was carried out under the protection of an argon atmosphere, the ball milling time was 3h, the ball-to-material ratio (i.e., the ratio of the mass of the steel ball to the total mass of the two raw materials, magnesium hydride powder and carbon-loaded elemental nickel and cobalt powder) was 30:1, the rotation speed was 400r / min, and nano-magnesium hydride / reduced graphene oxide loaded nickel-copper alloy powder was obtained, thereby obtaining a nano-magnesium hydride-based hydrolysis hydrogen production material.
[0049] The present invention adopts the water displacement substitution method to determine the hydrolysis performance of the MgH2-based composite material. An electronic balance is used to measure the mass of water replaced by the escaped hydrogen, and the balance reading is the volume of hydrogen produced by hydrolysis. The volume of H2 produced by hydrolysis is equal to the balance reading. The electronic balance is connected to a computer, and the computer can automatically record data and reaction time. In this experiment, the hydrogen yield of the entire sample is calculated by hydrolyzing 0.1g of the composite sample, and then converted into the hydrogen yield under standard conditions by the ideal gas equation. HGR (hydrogen generation rate) refers to the instantaneous hydrogen release rate of the sample, and the maximum value obtained from the differential curve of the hydrogen production changing with time is mHGR (the same below).
[0050] The nano-magnesium hydride-based hydrolysis hydrogen production material prepared by using the reduced graphene oxide-loaded nickel-copper alloy composite material provided in this embodiment has a final hydrogen release amount of 1677.4 mL g in 0.05 mol / LMgCl2 solution at 30 °C within 10 min. -1 , the hydrogen release efficiency is 98.49%.
[0051] Figure 1 This is the X-ray diffraction (XRD) spectrum of the magnesium hydride and reduced graphene oxide-loaded nickel-copper alloy composite material after ball milling in Example 1. It can be seen from the figure that the phase components of the composite material are nickel-copper alloy and magnesium hydride. Figure 2This is a FESEM spectrum of the reduced graphene oxide loaded nickel-copper alloy composite material prepared in Example 1. From the figure, it can be seen that the reduced graphene oxide carrier and the nickel-copper alloy particles attached to its surface, and the alloy particles are evenly distributed. Figure 3 This is the HRTEM spectrum of the reduced graphene oxide loaded nickel-copper alloy composite material prepared in Example 1. From the figure, it can be seen that the reduced graphene oxide carrier and the nickel-copper alloy particles attached to its surface, and the alloy particles are relatively small in size. Figure 4 This is the EDS spectrum of the reduced graphene oxide loaded nickel-copper alloy composite material prepared in Example 1. It can be seen from the figure that the nickel and copper elements are very evenly dispersed, and the distribution of the carbon element is consistent with the FESEM morphology image.
[0052] It can be seen that the catalyst performance of this embodiment is good, partly because the reduced graphene oxide loaded nickel-copper alloy composite material is more evenly dispersed after being treated with a suitable ball milling time, and is well combined with magnesium hydride.
[0053] Comparative Example 1
[0054] A reduced graphene oxide loaded elemental nickel composite material, wherein the mass ratio of the elemental nickel to the graphene oxide is 1:1.65.
[0055] 50 mL of methanol was added to Ni(NO3)2·6H2O (1427.6 mg), GO (400 mg) and PVP (8 mg), and ultrasonic oscillation was performed until all of them were dissolved to form a transparent solution, and then stirred for 6 h. The solution was then placed in a blast oven and dried for 24 h to obtain Ni@GO. The Ni@GO powder prepared above was spread in a crucible, placed in a tubular furnace, and heated at 5 °C min-1 under a H2 / Ar atmosphere. -1 The mixture was heated to 500 °C at a heating rate of 1.5 °C and kept at that temperature for 4 h before being cooled naturally to obtain the Ni@rGO catalyst.
[0056] The catalytic performance of the prepared reduced graphene oxide loaded nickel composite material was tested: 0.92g of magnesium hydride powder and 0.08g of reduced graphene oxide loaded nickel composite material were put into a ball mill, wherein the ball milling process was carried out under the protection of argon atmosphere, the ball milling time was 3h, the ball-to-material ratio (i.e., the ratio of the mass of the steel ball to the total mass of the two raw materials, magnesium hydride powder and reduced graphene oxide loaded nickel powder) was 30:1, the rotation speed was 400r / min, and nano magnesium hydride / reduced graphene oxide loaded nickel powder was obtained, thereby obtaining nano magnesium hydride-based hydrolysis hydrogen production material.
[0057] The final hydrogen release rate of the nano-magnesium hydride-based hydrolysis hydrogen production material prepared by using the above-mentioned reduced graphene oxide-supported elemental nickel catalytic material in 0.05 mol / LMgCl2 solution at 30°C within 10 min was 1235 mL g -1, the hydrogen desorption efficiency is 72.5%. It can be seen that when the reduced graphene oxide in the catalyst only loads elemental nickel, its catalytic efficiency is significantly low.
[0058] Comparative Example 2
[0059] A reduced graphene oxide-loaded elemental copper composite material, wherein the mass ratio of elemental copper to graphene oxide is 1:1.65.
[0060] 50 mL of methanol was added to Cu(NO3)2·3H2O (1186 mg), GO (400 mg) and PVP (8 mg), and ultrasonic oscillation was performed until all of them were dissolved to form a transparent solution, and then stirred for 6 h. The solution was then placed in a blast oven and dried for 24 h to obtain Cu@GO. The Cu@GO powder prepared above was spread in a crucible, placed in a tubular furnace, and heated at 5 °C min-1 under a H2 / Ar atmosphere. -1 The mixture was heated to 500 °C at a heating rate of 1.5 °C and kept at that temperature for 4 h before being cooled naturally to obtain the Cu@rGO catalyst.
[0061] The catalytic performance of the prepared reduced graphene oxide-loaded copper composite material was tested: 0.92 g of magnesium hydride powder and 0.08 g of reduced graphene oxide-loaded copper composite material were put into a ball mill, wherein the ball milling process was carried out under the protection of an argon atmosphere, the ball milling time was 3 h, the ball-to-material ratio (i.e., the ratio of the mass of the steel ball to the total mass of the two raw materials, magnesium hydride powder and reduced graphene oxide-loaded copper powder) was 30:1, the rotation speed was 400 r / min, and nano magnesium hydride / reduced graphene oxide-loaded copper powder was obtained, thereby obtaining a nano magnesium hydride-based hydrolysis hydrogen production material.
[0062] The final hydrogen release rate of the nano-magnesium hydride-based hydrolysis hydrogen production material prepared by using the above-mentioned reduced graphene oxide-supported elemental copper catalytic material in 0.05 mol / LMgCl2 solution at 30°C within 10 min was 1344.6 mL g -1 , the hydrogen desorption efficiency is 78.95%. It can be seen that when the reduced graphene oxide in the catalyst only loads single copper, its catalytic efficiency is obviously low.
[0063] Comparative Example 3
[0064] 1.00 g of magnesium hydride powder was put into a ball mill, wherein the ball milling process was carried out under the protection of an argon atmosphere, the ball milling time was 5 h, the ball-to-material ratio (i.e., the ratio of the mass of the steel ball to the mass of the magnesium hydride powder) was 30:1, and the rotation speed was 400 r / min to obtain nano magnesium hydride powder.
[0065] The final hydrogen release amount of the nano-MgH2-based powder in 0.05 mol / LMgCl2 solution at 30°C within 10 min was 1133.4 mL g -1, the hydrogen release efficiency is 66.55%. It can be seen that without adding any catalyst, the hydrolysis hydrogen release efficiency of magnesium hydride powder is very low.
[0066] The difference between Example 1 and Comparative Examples 1-3 is that Example 1 uses reduced graphene oxide loaded copper-copper alloy composite material as a catalyst to test the catalytic performance, Comparative Example 1 uses reduced graphene oxide loaded elemental copper catalytic material as a catalyst to test the catalytic performance, and Comparative Example 2 uses reduced graphene oxide loaded elemental copper catalytic material as a catalyst to test the catalytic performance; Comparative Example 3 uses the hydrolysis hydrogenation performance of magnesium hydride powder without adding any catalyst.
[0067] In addition, the composite catalyst prepared by the present invention contains alloy particles, namely copper copper particles, Figure 3 It can be seen from the medium-scale data and particle size that the copper-copper alloy particles are well loaded and dispersed on the reduced graphene oxide, and the particle size is small, about 20-100nm.
[0068] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A bimetallic composite catalyst for hydrogen production by hydrolysis, the catalyst being a reduced graphene oxide-supported nickel-copper alloy composite catalyst, wherein the reduced graphene oxide is doped with nickel-copper alloy particles; wherein: The mass percentage of the reduced graphene oxide is 30%-50%, and the mass percentage of the nickel-copper alloy is 50%-70%; The bimetallic composite catalyst for producing hydrogen by hydrolysis is prepared by the following method: (1) adding a nickel source, a copper source, a carbon source and a surfactant into an organic solvent, ultrasonically vibrating until all of them are dissolved to form a transparent solution, and then stirring to obtain a solution A; (2) placing solution A in a forced air oven for drying to obtain a composite catalyst precursor; (3) The composite catalyst precursor is calcined at a temperature of 450-550° C. in a mixed atmosphere of hydrogen and argon to obtain a bimetallic composite catalyst.
2. A method for preparing the bimetallic composite catalyst for producing hydrogen by hydrolysis according to claim 1, comprising: (1) adding a nickel source, a copper source, a carbon source and a surfactant into an organic solvent, ultrasonically vibrating until all of them are dissolved to form a transparent solution, and then stirring to obtain a solution A; (2) placing solution A in a forced air oven for drying to obtain a composite catalyst precursor; (3) The composite catalyst precursor is calcined at a temperature of 450-550° C. in a mixed atmosphere of hydrogen and argon to obtain a bimetallic composite catalyst.
3. The preparation method according to claim 2, wherein: In step (1), the nickel source is nickel nitrate hexahydrate; the copper source is copper nitrate trihydrate; the carbon source is graphene oxide; and the surfactant is polyvinyl pyrrolidone.
4. The preparation method according to claim 2, wherein: In step (1), the organic solvent is methanol, and the stirring method is magnetic stirring.
5. The preparation method according to claim 2, wherein: The drying conditions in step (2) are: drying temperature is 55-65°C, and drying time is 20-40h.
6. A nano magnesium hydride-based hydrolysis hydrogen production material, comprising: 90-94% by mass of magnesium hydride; The bimetallic composite catalyst for producing hydrogen by hydrolysis as claimed in claim 1 has a mass percentage of 6-10%; wherein: The bimetallic composite catalyst for hydrogen production by hydrolysis is a reduced graphene oxide-supported nickel-copper alloy composite catalyst; Both magnesium hydride and reduced graphene oxide-supported nickel-copper alloy composite catalysts are in powder form; The purity of magnesium hydride powder is above 99% and the particle size is less than 40μm.
7. A method for preparing the nano-magnesium hydride-based hydrolysis hydrogen production material according to claim 6, comprising: Pretreatment: mixing magnesium hydride powder with reduced graphene oxide-supported nickel-copper alloy composite catalyst powder to obtain a mixed powder; Post-treatment: ball mill the mixed powder under inert atmosphere for 1-8 hours, with a ball-to-material ratio of 25-35:1 and a rotation speed of 300-500 r / min to obtain nano-magnesium hydride-based hydrolysis hydrogen production material.
Citation Information
Patent Citations
Preparation method of porous copper-nickel alloy fiber
CN103498071A
Method for preparing nano Cu3.8 Ni alloy loaded on graphene by liquid phase reduction method
CN104475753A
Supported nickel-copper alloy nano-catalyst and preparation method thereof and application to catalytic hydrogenation
CN106179353A
Graphene-loaded copper and nickel / cerium oxide nanocomposite material, preparation method and ammonia borane catalytic decomposition method
CN106824211A
Nano-copper alloy / nitrogen-doped graphene composite catalyst and preparation method thereof
CN108330506A
